POWER FACTOR CONTROL IN LOW VOLTAGE ELECTRIC NETWORK IN OPTIMUM AND EFFICIENT POWER POSITION USING MICROCONTROLLER - , S.Kom., M.T, Sukenda; Hermawan, Wawan (International Journal of Psychosocial Rehabilitation, 2020)
Electrical energy is a very important requirement; interruption of electrical energy results in many activities that are interrupted and even stopped. Saving electricity is a necessity because, in the future, the supply of electrical energy can be limited. The act of reducing the use of electrical energy is the right solution. Electricity energy savings can be done in several ways: saving energy by turning off some electricity loads, saving energy by installing energy-saving electrical loads, and saving energy that does not reduce or install energy-efficient electrical loads but reduces or even eliminates all electric power. or increase the power factor of the inductive, energy-saving energy by installing capacitors in the circuit or electricity network. The installation of capacitors can also be useful to optimize the power installed on the electricity grid of PLN customers. The installation of capacitors on the electricity network must not be arbitrarily installed and must pay attention to the nature of the electrical load, which means that not all electrical loads can be repaired and must be repaired by the power factor. From this description, the authors build a power factor control prototype. This system is built to control the capacitors installed on the electricity network so that the capacitors are not installed in accordance with what is needed on the electricity network. In addition to this, the capacitor size must also be in accordance with the requirements on the network, so the microcontroller will direct how many capacitors must be installed with the help of a relay module. In order for the microcontroller to be able to control the relay module, there must be data coming in, namely by installing multiple PZEM-004t measuring devices. From the measurement data, it can be known whether the network requires capacitors or not, and if capacitors are required, how many capacitors must be installed on the electric network. With this system, consumers can optimize power in accordance with the amount of installed power that we buy from PLN, and besides that, we can find out the amount of voltage, current, and power used at that time.